Mechanical and tribotechnical properties of three-component solid lubricant UHMWPE composites; AIP Conference Proceedings; Vol. 2053 : Mechanics, Resource and Diagnostics of Materials and Structures (MRDMS-2018) - Panin S. V. Sergey Viktorovich; Kornienko L. A. Lyudmila Aleksandrovna; Valentyukevich N. N. Nataljya Nikolaevna; Aleksenko V. O. Vladislav Olegovich; Ovechkin B. B. Boris Borisovich (2018, 2018)
Title screen